Hubungan antara task aversiveness dengan prokrastinasi akademik - Linra, Magvirasari Lestari; nadjamuddin, Lukman; Fakhri, Nurfitriany (Jurnal Psikologi Pendidikan dan Konseling: Jurnal Kajian Psikologi Pendidikan dan Bimbingan Konseling, 2016)
The purpose of study was to determine the relationship of the task aversiveness with academic procrastination. Subject of the study were 100 students out of a population of 516 students of the Faculty of Psychology class of 2012-2014. The method used in this research is quantitative by using Spearman rho as data analysis techniques. The research instrument consists of academic procrastination scale and the scale of the task aversiveness. Based on the results of correlation is known that there is a positive relationship between task aversiveness with academic procrastination with a correlation coefficient r = 0.508; p = 0.000. The results showed that of the 100 students of the Faculty of Psychology University of Makassar has a degree of relationship between task aversiveness with academic procrastination is on the very low category (25, 8%). Area/types of tasks delayed is not necessarily an unpleasant task and otherwise unpleasant task may not be postponed. Area task the highest level of aversive and delays are areas the task of writing and reading. This study illustrates that academic procrastination can be lowered by a change in the mindset of an unpleasant task.